2019
DOI: 10.1021/acsbiomaterials.9b00721
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesized Gold Nanoparticles: In Vivo Study of Near-Infrared Fluorescence (NIR)-Based Bio-imaging and Cell Labeling Applications

Abstract: Near infrared (NIR) fluorescence imaging is a striking imaging modality for biomedical and clinical applications due to its deep tissue penetration and low phototoxicity. The major issue with NIR dyes is their non-specific distribution and requirement of tagging with biomolecules for specific tissue localization. Till now, there have been no imaging agents available that can distribute into a specific organ without the need for targeted ligands, which remains as an unmet clinical need. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
3
52
0
Order By: Relevance
“…To this end, our group already reported biosynthesized gold nanoparticles (AuZE), obtained by the reduction of gold salts using extracts of Zinnia elegans , that exhibit fluorescence at both the green (emission: 450 nm; excitation: 350 nm) and red regions (emission: 720 nm; excitation: 450 nm). The AuZE when injected intraperitoneally in C57BL6/J mice exhibited non-invasive NIR bioimaging (excitation: 710 nm; emission: 820 nm) [ 29 ]. However, these gold nanoparticles do not exhibit anticancer activity unless we use any chemotherapeutic drug.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, our group already reported biosynthesized gold nanoparticles (AuZE), obtained by the reduction of gold salts using extracts of Zinnia elegans , that exhibit fluorescence at both the green (emission: 450 nm; excitation: 350 nm) and red regions (emission: 720 nm; excitation: 450 nm). The AuZE when injected intraperitoneally in C57BL6/J mice exhibited non-invasive NIR bioimaging (excitation: 710 nm; emission: 820 nm) [ 29 ]. However, these gold nanoparticles do not exhibit anticancer activity unless we use any chemotherapeutic drug.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the above fundamental issues and knowing the anticancer activity of silver from various published literature, we designed and developed silver nanoparticles (AgZE) using the leaf extract of Zinnia elegans (ZE). The Zinnia elegans plant has been selected for biosynthesis as it emits fluorescence in the NIR region as per the published literature [ 29 ]. Additionally, the ZE plant has several medicinal values such as hepatoprotective, antifungal, antihelmintic, antimalarial, anti-infective, phytoremediation, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other interesting investigation, Popovtzer and group demonstrated conjugation of citrate reduced gold nanoparticles with 2-deoxy-d-glucose, which aids in penetration and accumulation in tumor cells and can be used as a diagnostic imaging tool for imaging tumor cells (US 10,478,132) [58]. Kotcherlakota et al demonstrated the synthesis of biocompatible AuNPs using aqueous leaf extract of Zinnia elegans and their applications toward in vivo near-infrared fluorescence (NIR)-based bioimaging and cell labeling applications in mouse B16F10 melanoma tumor model [29].…”
Section: Biosynthesized Gold Nanoparticles In Cancer Theranostics: Recent Advancements and Patentsmentioning
confidence: 99%
“…[ 1–3 ] Among them, noble metal NPs (gold, silver, and platinum NPs [PtNPs]) offer promising opportunity for various biomedical applications, including drug delivery, bioimaging, diagnostics, etc., owing to their distinctive physicochemical properties. [ 4–8 ] However, serious toxicological consequences might be observed on interaction of these NPs with the biological moieties at cellular and subcellular level. Based on this, several studies investigated potential toxicity of various nanomaterials, such as carbon nanotubes, graphene oxides, zinc oxides, cerium oxides, quantum dots, and silica NPs.…”
Section: Introductionmentioning
confidence: 99%